Practical Uses for Ultrasound in Managing Beef Cattle Reproduction - Mario Binelli; Thiago Martins; John Arthington; Kalyn Waters; Vitor Mercadante; Philipe Moriel; Angela Gonella-Diaza (EDIS)
This publication aims to discuss the use of ultrasound to assist with beef cattle reproduction, which includes evaluation of the pre-service status of heifers and cows, diagnosis of pregnancy, determination of fetal age and sex, and evaluation of reproductive fitness of embryo recipients. Written by Mario Binelli, Thiago Martins, John Arthington, Kalyn Waters, Vitor Mercadante, Philipe Moriel, and Angela Gonella-Diaza, and published by the UF/IFAS Department of Animal Sciences, revised April 2023.